Letting Go: Representation, Presentation, and Disney's Art of Animation. (July 2019) - Telotte, JP
This article considers two linked developments in Disney animation at a major point of change for the studio. One is the effort to craft a new 'logistics of perception' or way of seeing and appreciating Disney's work in this period. Prompting that effort is the other, a shift from the studio's early emphasis on realistic representation, or an 'illusion of life', to what might be termed a presentational approach that repackaged Disney animation and re-framed its experience. These developments, observed in episodes of the Disneyland TV series of the 1950s–1960s dedicated to 'the art of animation', anticipate the emergence of new styles in Disney animation and of a new approach to animation that would eventually be reflected in the development of audio-animatronics and theme parks.